Transvaginal sonography versus saline infusion sonohysterography, which has better diagnosing accuracy in detecting cause of abnormal uterine bleeding in perimenopausal women? - ., Saika; Singh, Tania (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Saline infusion sonohysterography (SIS) is a simple, safe, reliable, effective and well-tolerated method without complications that complements transvaginal sonography (TVS) in the pre-operative examination of uterine pathology. SIS has been found to be superior to TVS in most studies that have compared their effectiveness in detecting intracavitary lesions and has also been found to decrease the number of diagnostic hysteroscopies to as much as 50%. Patients in whom no intracavitary abnormality is detected by SIS require no further evaluation and are best treated with medical therapy. Methods: The observational study was conducted in the postgraduate department of gynaecology and obstetrics, Lalla Ded Hospital, Government Medical College Srinagar. All consecutive patients with perimenopausal abnormal uterine bleeding attending gynaecology OPD were enrolled in the study after taking informed written consent. Results: SIS has better accuracy than TVS in diagnosing the cause of AUB in perimenopausal women. TVS had sensitivity, specificity and PLR of 60 and 93.8, 9.8, respectively for fibroids while polyps had 27.3, 98.8 and 17.5, respectively, AUP had 81.8, 79.2, 3.9 respectively. SIS had sensitivity, specificity, PLR and NLR values of 80.0, 96.9, 40.7 and 0.21, respectively for diagnosing fibroids, while 63.6, 98.4, 26 and 0.37 respectively for polyp, and 90.9, 94.3, 16.1 respectively for AUP. Conclusions: Accuracy of SIS as a test for detecting pathology in AUB in perimenopausal patients is moderately good and suitable for developing countries.